2008
DOI: 10.1007/s00330-008-1203-7
|View full text |Cite
|
Sign up to set email alerts
|

Coronary CT angiography using 64 detector rows: methods and design of the multi-centre trial CORE-64

Abstract: Multislice computed tomography (MSCT) for the noninvasive detection of coronary artery stenoses is a promising candidate for widespread clinical application because of its noninvasive nature and high sensitivity and negative predictive value as found in several previous studies using 16 to 64 simultaneous detector rows. A multi-centre study of CT coronary angiography using 16 simultaneous detector rows has shown that 16-slice CT is limited by a high number of nondiagnostic cases and a high false-positive rate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 62 publications
2
102
0
10
Order By: Relevance
“…The complete CORE-64 protocol and methods have been previously described ( 6,16 ). Inclusion criteria were symptomatic patients who were at least 40 years old, were scheduled for CCA, and were willing to provide written informed consent.…”
Section: Cardiac Imaging: Multidetector Ct Angiography Of Coronary Armentioning
confidence: 99%
“…The complete CORE-64 protocol and methods have been previously described ( 6,16 ). Inclusion criteria were symptomatic patients who were at least 40 years old, were scheduled for CCA, and were willing to provide written informed consent.…”
Section: Cardiac Imaging: Multidetector Ct Angiography Of Coronary Armentioning
confidence: 99%
“…This observational evidence has now been corroborated by 2 multicenter clinical trials of the diagnostic accuracy of CCTA (26,27). In the former trial (26), 230 patients underwent CCTA and invasive coronary angiography (59% men; mean age, 57 y).…”
Section: Multicenter Clinical Trials With Cctamentioning
confidence: 84%
“…A plenty of studies demonstrated the high diagnostic accuracy of CCT (Table 2) in the diagnostic workup of patients with suspected CAD (3)(4)(5)8,11,(79)(80)(81)(82)(83) and low to intermediate risk of CAD (6,84). CCT was also validated by several outcome studies that investigated risk stratification and prognostic value in registry data (85)(86)(87).…”
Section: Diagnostic Performancementioning
confidence: 95%